MIKROPROPAGASI PISANG MAS KIRANA (Musa acuminata L) MEMANFAATKAN BAP DAN NAA SECARA IN-VITRO - Kasutjianingati, Kasutjianingati; Boer, Dirvamena (Jurnal Agroteknos, 2013)
The aim of this research was to study the effects of cytokinine and auxin (BAP and NAA) on micropropagation of banana cv Mas Kirana (AA). The experiment used completely randomized design, with a single factor of multiplication media, consisted of 4 media i.e. MS + BAP 4 ppm, MS + BA 6 ppm, MS + BAP 4 ppm + NAA 0,1 ppm, MS + BA 6 ppm + 0.1 ppm. The experiment treatment of BAP 4 ppm produced the highest shoot number (100% small bud). The best shoot of Mas Kirana morphogenesis produced when the shoots sub-cultured in media MS0. The treatment 4 ppm BAP after sub-cultured at MS0 produced big plantlet ready to acclimatization for up to 43% (9 plantlets). Key words: BAP, NAA, morphogenesis, big plantlet